2007
DOI: 10.1002/pts.802
|View full text |Cite
|
Sign up to set email alerts
|

Quality of orange juice in barrier packaging material

Abstract: The vitamin C content and the colour of orange juice made from concentrate were measured during 9 months of storage at 20°C either under artifi cial light or in darkness. The packaging materials used were glass, standard monolayer polyethylene terephthalate (PET) and multilayer PET (PET/nylon and oxygen scavenger/PET) containers. In this experiment, all bottles were sealed with aluminium foil in order to avoid any cap effect. The results showed that in plastic packaging materials, the loss of vitamin C was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…However, the production and use of glass bottles have negative environmental effects due to their manufacturing energy costs; they are easily broken and are comparatively heavy (Table 1). Numerous studies based on the use of different packaging materials have been reported to overcome these problems [17,18].…”
Section: Influence Of Packaging On Beverage Conservation and Drawbackmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the production and use of glass bottles have negative environmental effects due to their manufacturing energy costs; they are easily broken and are comparatively heavy (Table 1). Numerous studies based on the use of different packaging materials have been reported to overcome these problems [17,18].…”
Section: Influence Of Packaging On Beverage Conservation and Drawbackmentioning
confidence: 99%
“…However, oxygen also diffuses from the surrounding atmosphere through the packaging material into the beverage with a rate depending on the permeability of the material and the difference in oxygen partial pressure on both sides of the packaging. Therefore, appropriate barrier materials should be selected to avoid oxidative degradation, such as glass bottles, foil laminates in carton packs (e.g., Tetrapak) or flexible pouches, and polyethylene terephthalate (PET) bottles in the case of juice [17,23,24]. Bacigalupi et al [20] investigated the sensitivity to oxidation of orange juice through packaging in standard or active PET with oxygen scavenger bottles.…”
Section: Influence Of Packaging On Beverage Conservation and Drawbackmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these properties are necessary in order to preserve organoleptic food quality during its shelf life because they prevent the alteration of food due to excessive oxygen or water vapor transference or the loss of aromatic compounds. [2,3] Much work has been undertaken to improve PLA transport and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%